Pelaksanaan Perlindungan Terhadap Sumberdaya Perikanan dalam Laut Teritorial dan Zona Ekonomi Ekslusif Indonesia di Provinsi Aceh - Fikri Fikri (Universitas Syiah Kuala, 2013)
ABSTRACT: This research aims to explore how the protection on fishery in the Indonesian territorial and Economy Exclusive Zone in Aceh and obstacles faced by the government in providing the protection on fishery resources in Aceh. Descriptive analytical method is applied to describe and find the legal facts wholly relating to the protection. The research shows that the implementation of monitoring in terms of conducting the laws has obstacles especially regarding the staffs monitoring it, patrol vessels and budget in monitoring the protection. It is expected that the government should add more staff and providing enough supporting facilities for the law enforcers in fishery field hence the rules can be enforced and the resource can guarantee the need of next generations. The Protection on Fishery Resources at the Indonesian Territorial and Exclusive Economy Zone in Aceh